The organizational socialization process of nonprofit workers - Roth, Emily (Kansas State University, 2017)
A commonly held belief in higher education is that a student’s educational program paves the way towards a specific career choice, forcing students to intentionally choose courses in preparation for a particular line of work (Lair & Wieland, 2012). Recognizing the influential role of education (Jablin, 2001) and the increasing numbers of nonprofit education programs (Mirabella & McDonald, 2012), it is important to understand the educational expectations created by university programs and how these expectations are enacted as students become nonprofit employees. To better understand communication practices that shape the expectations, experiences, and worker identities, this study applies organizational assimilation theory to nonprofit education and work through interviews of nonprofit employees’ experiences after completing a nonprofit education program. Qualitative analysis of the interview transcripts indicates that nonprofit-focused educational programs socialize students to work for a cause that they find personally meaningful. However, not all students are able to meet this expectation, creating two paths, a straight path and a winding path in search of meaningful work. Those on the straight path who found personally meaningful work attributed their experience to an internal locus of control based on an intentional job search and workplace opportunities. Participants who did not find the personally meaningful work they expected used external control attributions by blaming the job market, the way their generation approaches work, and how their educational program created unrealistic expectations. Findings deepen understandings of organizational assimilation theory in terms of education, while bridging educational practices and organizational assimilation theory to contribute practical implications. Practical implications include encouraging education programs to facilitate volunteering and networking opportunities for their students, prospective nonprofit workers to seek out volunteer and job shadowing opportunities, and nonprofit organizations to focus on the assimilation process of new employees.
Keywords: organizational socialization; higher education; nonprofit work; meaningful work